THe EFFECTIVENESS WATER INTRODUCTION LEARNING MODEL (MNS) BASED ON PLAY IN SWIMMING SPORT - Maryam Novita Sary (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2019)
The purpose of this study is to produce a water-based learning introduction model (MNS) based on playing in swimming (for elementary school students who have anxious swimming). The subjects in this research and development are Bekasi Jaya XXIII Elementary School and AL-AZHAR Kelapa Gading Islamic Elementary School. The research method used is the research and development model of Borg and Gall. Data collection techniques used are the results of expert validation and effectiveness testing through an instrument of anxiety level assessment with t-test statistical data analysis. The results of research and development of water-based learning recognition models (MNS) based on swimming in swimming (for elementary school students who have anxious swimming) shows that (1) water-based learning models (MNS) are based on playing in swimming sports (for elementary school students who are anxious swimming) significantly reduce the level of anxiety in the learning process of water recognition in swimming sports, (2) Based on data analysis, the average value of pre-test is 14.5 and the post-test average is 8.1, t-count = 25.59, df = 39 and p-value = 0.00 <0.05, it can be said that the water recognition learning model (MNS) based on playing in swimming (for elementary school students who have the anxiety to swim) can reduce the level of anxiety and is effective to be applied in the learning process of learning water in swimming sports.